The effect of training, work environment, motivation, job satisfaction, and career satisfaction on employee productivity - Ichdan, Dany Amrul (Annals of Management and Organization Research, 2024)
Purpose: The purpose of this study was to examine the effect of training and work environment on employee productivity, with motivation, job satisfaction, and career satisfaction as intervening variables in the education sector. Research Methodology: This study employs a quantitative methodology and survey data collected from 300 employees working in various educational institutions. Structural Equation Modeling (SEM) via Smart PLS was used to analyze the relationships between the variables. Results: The findings reveal that Both training and work environments have a significant positive impact on employee productivity. In addition, motivation, job satisfaction, and career satisfaction play critical intervening roles in enhancing employee productivity. The analysis shows that well-structured training programs and a conducive work environment significantly boost employee motivation and satisfaction levels, which, in turn, improve overall productivity. Contribution: This study contributes to the literature by highlighting the importance of training and work environments in the education sector, particularly focusing on the mediating effects of motivation, job satisfaction, and career satisfaction. Originality: The originality of this research lies in its comprehensive approach to understanding the complex interplay between these variables, offering valuable insights for educational institutions that aim to enhance employee performance and productivity. These results underscore the need for targeted interventions in training and work environment improvements to foster a more motivated, satisfied, and productive workforce in the education sector.